#BlackDontCrack: a content analysis of the aging Black woman in social media. Issue 1 (2nd January 2018) - Mondé, Geniece Crawford
Abstract: This paper examines how positive social media representations of aging Black female bodies problematize existing notions of aging as an almost uniformly negative phenomenon. Using the social media platform Tumblr, this study reveals that the framing of age, race, and gender is both complex and nuanced. Images which challenge deeply set historical notions of female beauty include those of celebrities, noncelebrities and comparisons between aging Black women and historically standardized representations of physical attractiveness. Findings illustrate that managing impressions vis-à-vis social media is a complex, sometimes messy performance in which images both challenge and substantiate problematic assumptions. Some images that framed Black women positively but did so at the expense of other women. This paper adds to the body of work that explores how social media is used as a vehicle for counter narrative messaging. These findings offer additional insight into how impression management theory is used to analyze social media content.